40.3k views
2 votes
How do you do,
csc2x-cot2x = tanx

User Ksuralta
by
8.3k points

1 Answer

2 votes

csc2x-cot2x=tanx \\ \\ ((1)/(2)cscxsecx) -( (cotx-tanx)/(2) )=tanx \\ \\ ((cscxsecx)/(2)) -( (cotx-tanx)/(2) )=tanx \\ \\ (( (1)/(sinx) (1)/(cosx) )/(2)) -( (cotx-tanx)/(2) )=tanx \\ \\ ((1)/(2(sinxcosx))) -( (cotx-tanx)/(2) )=tanx \\ \\ ((1)/(2(sinxcosx))) -( ((sinxcosx)*cotx-tanx)/(2*(sinxcosx)) )=tanx \\ \\ (1-(cos^2x-sin^2x))/(2(sinxcosx)) =tanx \\ \\ (1-cos^2+sin^2x)/(2(sinxcosx))=tanx


(sin^2x+sin^2x)/(2(sinxcosx)) =tanx \\ \\ (1-cos2x)/(sin2x) =tanx \\ \\ (sin2x)/(cos2x+1)=tanx \\ \\ tanx=tanx


User Mattfred
by
7.8k points

Related questions

asked Jul 10, 2024 186k views
Danypata asked Jul 10, 2024
by Danypata
9.2k points
1 answer
5 votes
186k views
asked Oct 26, 2017 170k views
JBibbs asked Oct 26, 2017
by JBibbs
7.9k points
1 answer
2 votes
170k views
2 answers
2 votes
160k views